The Influence of The Big Book Media Based Discovery Learning Learning Model on Learning Outcomes on Theme 7 Technological Development Class III Agia Sophia Private Elementary School - Tarigan, Rosenda Ita; Silaban, Patri Janson; Sari HS, Dyan Wulan; Abi, Antonius Remigius; Pinem, Irmina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
This research aims to determine the effect of using the Discovery Learning learning model based on Big Book media on student learning outcomes on theme 7 Technological developments in class III of Agia Sophia Private Elementary School for the 2023/2024 academic year. This research used quantitative methods, sampling using purposive sampling and the sample used was class III, totaling 30 students. The results of this research show that student learning outcomes using the Discovery Learning model based on Big Book media are in the very good category with an average of 80.3 with a correlation test result of 0.846, which means rcount (0.846) ≥ rtable (0.367), so Ha is accepted. So there is a strong influence between the use of the Discovery Learning learning model based on Big Book media on student learning outcomes in theme 7 Technological developments in class III of Agia Sophia Private Elementary School for the 2023/2024 academic year. It can be seen from the results of the T-test research where tcount ≥ ttable, namely 8.403 ≥ 2.048 so it can be stated that Ha is accepted. This shows that there is a significant positive influence from the use of the Discovery Learning learning model based on Big Book media on student learning outcomes in theme 7 Technological developments in class III of Agia Sophia Private Elementary School for the 2023/2024 academic year.